2013
DOI: 10.1080/03055698.2013.767184
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive style and gender differences in children’s mathematics achievement

Abstract: Males are often found to outperform females in tests of mathematics achievement and it has been proposed that this may in part be explained by differences in cognitive style. This study investigated the relation between Wholistic-Analytic and Verbal-Imagery cognitive style, gender and mathematics achievement in a sample of 190 Australian primary school students aged between 8-11 years (M = 9.77, SD = 1.05). It was hypothesised that males would outperform females in mathematics achievement tests, and that gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
1
14
1
5
Order By: Relevance
“…In other words, gender is considered as a social construction and gender differences are considered contextually and non-permanently bound, as they are not genetic [9]. Based on some studies, for example, the study conducted at Australian elementary school students on the students aged 8-11 years, the mathematical ability of boys is superior to girls [10]. This is similar to the research of mathematical ability in elementary school students in Germany [11].…”
Section: Introductionsupporting
confidence: 60%
“…In other words, gender is considered as a social construction and gender differences are considered contextually and non-permanently bound, as they are not genetic [9]. Based on some studies, for example, the study conducted at Australian elementary school students on the students aged 8-11 years, the mathematical ability of boys is superior to girls [10]. This is similar to the research of mathematical ability in elementary school students in Germany [11].…”
Section: Introductionsupporting
confidence: 60%
“…Male and female students seem to differ in their learning preference [19] and in the technology they prefer to use [20], [21]. However, data on gender differences are not conclusive because of changes in the attitudes toward ICT as a result of increased ICT universality in society [22].…”
mentioning
confidence: 91%
“…Differences between male and female students' learning preferences [19], types of ICT-supported activities [28], and ICT attitudes and opinions [24], [27] are reported. Male students are more often interested in ICT use [25], and use the computer more often for leisure activities [28].…”
Section: Gender and Ict Usementioning
confidence: 99%
“…In this study we also looked for possible relationship between participants' EFL achievement and their self-evaluation on the cognitive test. It should be noted that although many scholars (Arnup, Murrihy, & Roodenburg, 2013;Oxford, Nyikos, & Ehrman, 1988) have highlighted the importance of gender as a factor, the results are severely inconsistent. Furthermore, findings of those studies in the realm of EFL which have investigated the role of gender with respect to cognitive styles have yielded less consistent results (e.g., Saricaoglu & Arikan, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Nonetheless, it is not true for all cultures (Kaylani, 1996). On the other hand, Arnup, Murrihy, & Roodenburg (2013), suggested that cognitive styles affect boys and girls differently. With respect to learning style and reasoning, Severiens, Dam, & Nijenhuis (1998), found no significant difference between the two genders.…”
Section: The Role Of Gendermentioning
confidence: 99%